FILM DOKUMENTER NELAYAN ANAK BAGAN PANTAI GANDORIAH KOTA PARIAMAN - FIKRI HAMDANI, Dr. Syafwandi, M.Sn., San Ahdi, S.Sn., M.Ds. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
The film aims to publish fishing chart fisherman in the process of catching fish in the open seas. Marine is an activity carried out by generations by some people who life in over coast.In the process, many effort to obtain maximum result, marine is an effort made by some fisherman who lead by a captain (tunganai). Methodology used is with the approach analysis 5W+1H.The documentary film publication supported by some other media, such as clothes, calendars, stickers, wall clocks, pins, key chain, CD covers, label CDs and mug.Keywords : Documenter fils, Fisherman, Marine, Publication, Gandoriah Beach. Pariaman City.